Dynamics Characteristic Analysis of Spur Gear Pairs based on Tooth Surface Friction - Lu Fengxia; Wang Haofei; Zhu Rupeng; Bao Heyun; Jiang Huihui (Jixie chuandong)
A bending-torsional nonlinear dynamics model of the spur gear pair with 6-DOF is established and the dimensionless dynamics equations are derived.The tooth surface friction,time-varying stiffness,gear backlashes as well as gear mesh errors are considered in this model.Based on the location of the contact line,the mathematical expressions of the tooth surface friction and the friction torque are both derived.The effects of tooth surface friction on the dynamic behaviors of the system are studied.The results show that the tooth surface friction can increase the vibration of the system,and the effect is more obvious on the vibration in the perpendicular direction to the meshing line.The degree of the chaotic motion of the system can be reduced by the tooth surface friction,and the bifurcation of the system becomes blurred at the high meshing frequency and chaotic motion appears earlier by the tooth surface friction.